Bax, but notbcl-2, influences the prognosis of human pancreatic cancer. Issue 3 (1st September 1998) - Friess, H; Lu, Z; Graber, H U; Zimmermann, A; Adler, G; Korc, M; Schmid, R M; Büchler, M W
Abstract : Background — bcl-2 and bax belong to the bcl-2 -related gene family, which marks a new class of genes that influence apoptosis. The bcl-2 oncogene acts as a broad antiapoptotic factor and extends both normal and tumour cell survival. In contrast, the bax gene is a promoter of apoptosis. Aims —To analyse the expression of bcl-2 and bax in pancreatic cancer and correlate the results with clinical parameters. Patients —Pancreatic cancer tissue samples were obtained from 28 female and 32 male patients (median age 63, range 43–79 years) having surgery for pancreatic cancer. Normal pancreatic tissues obtained from 18 previously healthy organ donors served as controls. Methods —The levels of bcl-2 and bax mRNA expression were analysed by northern blot and the exact site of mRNA transcription was determined by in situ hybridisation. The presence of the corresponding proteins was determined by immunohistochemistry. Results —Northern blot analysis indicated that, in comparison with the normal pancreas, bcl-2 mRNA was overexpressed in 30% and bax mRNA in 61% of the pancreatic cancer samples. Concomitant overexpression of bcl-2 and bax was present in 26% of the cancer samples. Pancreatic adenocarcinomas exhibited 3.7-fold and 5.4-fold increases (p<0.001) in bcl-2 and bax mRNA levels respectively. In situ hybridisation showed that both bcl-2 and bax mRNA were expressed in the cancer cells. Immunohistochemical analysis showed positive Bcl-2 and Bax immunostaining in 28 and 83% of the cancer samples respectively. In multivariate analysis (Cox regression model), bax expression was found to be a strong indicator of survival (p<0.001). Patients whose tumours exhibited Bax immunostaining lived significantly longer (12 months) than those whose tumours were Bax negative (five months) (p<0.039). In contrast, no relation was found between Bcl-2 and survival time. Conclusions —The data indicate that genes that are involved in the regulation of apoptosis are upregulated in human pancreatic cancer cells. Prolonged survival times in patients in whom apoptosis promoting factors are upregulated indicate that apoptotic pathways are of biological significance in pancreatic cancer.